Nuevos registros del escarabajo indoafricano Digitonthophagus gazella (Fabricius 1787) (Coleoptera: Scarabaeinae) en Colombia (2016)
The Indo-african beetle Digitonthophagus gazella was introduced into the Americas as a bio-controller of parasites and flies in livestock systems. This dung scarab is characterized for its high dispersal ability, reproduction and efficient use of cattle manure. In Colombia, the most recent survey situated this beetle only in lowland areas. In the present study D. gazella was found in two new Colombian departments (Meta and Valle del Cauca) and its presence was confirmed in Antioquia. In this study, few individuals were collected and they were associated with vegetation systems with poor cover, such as livestock pastures and sugar cane monoculture, suggesting early stages of colonization and corroborating the preference of the species for open areas. Besides with the range extension with new records, this work also provides insights on D. gazella apparent colonization above 500 m of altitude. The distribution of this species across the Magdalena River valley appears to be associated with inter-department bovine transport. The importance of a continuous monitoring of the dispersion of D. gazella in Colombia, to establish its dispersal rate, habitat preference and pest status is also highlighted.